Composite Beams of Steel and Lightweight Concrete - Benjamin, Irwin A. (Engineering Journal, 1965)
Since publication of the 1961 AISC Specification, interest in composite design has grown. Concurrent with this growth in interest has been the development of new types of shear connectors and the use of composite design with lightweight concrete floor slabs. Data from tests on lightweight aggregate concrete composite beams was not available in 1961 when the current AISC Specification was developed. Since that time tests have been run on beams with lightweight concrete, with satisfactory results. This paper has a twofold purpose: to discuss a general method of evaluating composite beam tests, and to review the data on the effectiveness of shear connectors in lightweight concrete composite beams.